Evaluating medicine prices, availability and affordability in Bangladesh using World Health Organisation and Health Action International methodology - Lombe Kasonde; David Tordrup; Aliya Naheed; Wu Zeng; Shyfuddin Ahmed; Zaheer- (BMC, 2019)
Abstract Background Previous studies have shown limited availability of medicines in health facilities in Bangladesh. While medicines are dispensed for free in public facilities, they are paid out-of-pocket in private pharmacies. Availability, price and affordability are key concerns for access to medicines in Bangladesh. Methods The World Health Organization/Health Action International survey methodology was used to determine price, availability and affordability of 61 lowest price generic (LPG) and originator branded medicines in public facilities, private retail pharmacies and private clinics across 6 regions of Bangladesh. Medicines for non-communicable and infectious diseases, and both on and off the national Essential Medicines List were included. Prices were compared internationally using Median Price Ratio (MPR). Results Mean LPG (originator brand) availability in the public sector, private retail pharmacies, and private clinics was 37%, 63 (4) percent, and 54 (2) percent, respectively. Medicines for Non-Communicable Diseases (NCD) and essential medicines were significantly less available than infectious disease medicines and non-essential medicines, respectively. Mean LPG (originator brand) MPR was 0.977 in the public sector, 1.700 (3.698) in private retail pharmacies and 1.740 (3.758) in private clinics. Six medicines were expensive by international standards across all sectors. The least affordable treatments in both private sectors were bisoprolol (hypertension), metformin (diabetes) and atorvastatin (hypercholesterolemia). Conclusion Availability and affordability of NCD medicines are key concerns where the burden of NCD is rising. These findings show improvement from earlier studies, but room for further advances in availability and affordability of NCD medicines in Bangladesh. A small number of medicines are consistently expensive across sectors in Bangladesh, suggesting the need for strategies to address prices for certain medicines.